FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2011-2013) - Abraham Deny Septian Widodo, 11.05.52.0187; Poerwati, Rr. Tjahjaning (Students Journal of Economic and Management, 2016)
This study aims to examine and analyze the factors - factors that affect stock returns in manufacturing companies. The population in this study are all companies listed on the Indonesia Stock Exchange in 2011-2013.The sampling technique was done by purposive sampling. Based on the purposive sampling obtained a sample of 124 companies. Data analysis technique used is multiple linear regression analysis. The results showed that each variable has a different effect, namely ROA, PBV provide positive and significant impact on stock returns, while DER, EPS, AG provide positive and significant influence on stock returns. Keywords: Â Â Return On Asset (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Book Value (PBV), Asset Growth (AG), dan Return Saham.